PEMANEN ENERGI LISTRIK DARI CURAH HUJAN MELALUI TRANSDUSER PIEZOELEKTRIK SECARA SERI DAN PARALEL - Arief Moonik; Jotje Rantung; Benny Maluegha (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2023)
Electrical energy has become one of the basic needs for the continuity of human activities. From time to time human activities continue to increase and the demand for electrical energy also increases. In order to overcome this, many innovations in electricity are needed to support the need for electricity. By utilizing rainfall that continues to exist every year, this research was carried out to obtain the performance of converting raindrop energy into electrical energy through piezoelectric circuits and different rainfall parameters. The method used in this research is an experimental method, where the pressure applied to the piezoelectric varies to produce a voltage. There are two types of tests carried out in this study, namely testing with a series circuit and testing with a parallel circuit of various height variations, including: 170 cm, 190 cm, 210 cm, 230 cm, 250 cm, and 270 cm. In testing series and parallel circuits, the highest output voltages are both at a height of 270 cm. However, when viewed from the whole experiment with ten variations to the six heights, the series circuit produces more average voltages than the parallel circuit. Keywords: Piezoelectric, Series Circuit, Parallel Circuit, Rain.